The smart analysis for workforce and organization management in corporate environment - Santhosh, T.; Aswin, K. (BOHR International Journal of Advances in Management Research, 2023)
The overall objective of all management practices is to get work done efficiently, at the lowest cost, in the best manner possible, using selected and trained personnel and machinery. Absolute best results cannot be achieved without the full effort of skilled employees with the best office equipment and a good harmonious office environment. Effectiveness in the successful execution of office tasks lies in the selection and use of office space. The facilities provided to do the work help to do the work in the best way. Office space is a prime factor for successful business execution. It is also clear that it does not come easily. When deciding on the suitability of a building, the manager should prepare a thorough checklist of requirements. Naturally, each business organization, department, and office has its own unique needs. Priority levels are assigned once the checklist is prepared. Discussing what is important, wanted, and useful with subordinates helps everyone get a sense of ownership while also demonstrating and confirming priority levels.